Balancing food security, nutrition, and sustainability: Evaluating diverse cropping patterns. Comparing diversified cropping patterns in Dinajpur, Bangladesh - Cheesman, Stephanie; Washiq, Faisal; Hossain, Akbar; Aonti, Annika Jahan; Rahman, Md. Mobinur; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2023)
This research brief summarizes results from a cropping systems diversification experiment after the first complete cropping cycle. The trial has been established by the Bangladesh Wheat and Maize Research Institute (BWMRI) in collaboration with the Transforming Agrifood Systems in South Asia (TAFSSA) Initiative in Dinajpur, Bangladesh in August 2022.